CROSS SCALE ANALYSIS FOR THE EFFECT OF PROCESS PARAMETERS ON THE GRAIN SIZE OF COLD ROLLING SPLINE - WANG Yong; YUAN HaiLin; ZHU ShiFan; ZHANG ZuFang; JIN Ping; ZHOU QingCheng (Jixie qiangdu)
Multi field and cross scale analysis is helpful to improve the forming quality and analyze the evolution law of microstructure in the process of spline forming, which has a very important guiding significance for process optimization, quality prediction and control. The thermal mechanical coupling model of cold rolling forming were established and simulated. The macro size of the simulation results and the evolution law of the microstructure in the forming process were analyzed, and the change trend of grain size under different process parameters was analyzed by changing the feed rate and friction coefficient. The influence of feed rate and friction factor on the grain size is obtained, which provided theoretical basis for further research on the evolution law of microstructure in materials and the integrated manufacturing of spline shape and properties.